In-work policies in Europe: Killing two birds with one store? - Olivier Bargain; Kristian Orsini (University of Essex, Institute for Social and Economic Research (ISER), 2004)
Earning an income is probably the best way to avoid poverty and social exclusion, hence the recent trend of promoting employment through in-work transfers in OECD countries. Yet, the relative consensus on the need for `making work pay' policies is muddied by a number of concerns relative to the design of the reforms and the treatment of the family dimension. Relying on EUROMOD, a EU-15 integrated tax-bene?t microsimulation software, we simulate two types of in-work bene?ts. The ?rst one is means-tested on family income, in the fashion of the British Working Family Tax Credit, while the second is a purely individualized low wage subsidy. Both reforms are built on the same cost basis (after behavioral responses) and simulated in three European countries which experience severe poverty traps, namely Finland, France and Germany. The potential labor supply responses to the reforms and the subsequent redistributive impacts are assessed for each country using a structural discrete-choice model. We compare how both reforms achieve poverty reduction and social inclusion (measured as the number of transitions into activity). All three countries present di?erent initial conditions, including institutional environment, existing tax-bene?t systems and distribution of incomes and wages. These sources of heterogeneity are exploited together with di?erent labor supply sensitivities to explain the cross-country di?erences in the impact of the reforms.
Keywords: C25; C52; H31; J22; 330; tax-benefit systems; in-work benefits; microsimulation; household labor supply; multinomial logit; Familienleistungsausgleich; Familienbesteuerung; Lohnsubvention; Wirkungsanalyse; Einkommensverteilung; Soziale Integration; Simulation; Arbeitsangebot; Armutspolitik; Finnland; Frankreich; Deutschland